An Investigation of Position Effects in Large-Scale Writing Assessments. (October 2014) - Qian, Jiahe
Position effect, the interaction between a test item's position in an exam booklet and examinees' performance, is always of concern in developing test instruments. This study is intended to explore the factors that have interactive effects with prompt position in large-scale writing assessments and to differentiate the impact of each factor. This study analyzed the 2007 National Assessment of Educational Progress writing assessment by comparing three types of p -value scores at the first and second item positions; mixed linear regression models were applied to explore the factors correlated with position effects in the writing assessment. Although examinee motivation was the leading predictor of position effects, the results showed that other factors, such as gender, school type, and teaching emphasis, could also be predictors of position effects in writing performance, and they could be further differentiated by grade and other demographics.